Empirical versus exogenous spatial weighting matrices - Fernández Vázquez, Esteban (European Regional Science Association, 2010)
The traditional approach to estimate spatial models bases on a preconceived spatial weights matrix to measure spatial interaction among locations. The a priori assumptions used to define this matrix are supposed to be in line with the
10419/118909
Keywords: Kongressbeitrag; Graue Literatur; spatial econometrics; maximum entropy econometrics; weighting matrix specification; Monte Carlo simulations